Os usos de porém em artigos de opinião contemporâneos do Brasil - Borges, Andréa Lopes (2012)
This research contemplates the uses of porém in contemporaries opinion articles of Brazil. We decided to investigate the uses of this linguistic element because we saw necessity in specify your functioning, in view of that, while, on the one hand, there are adverbial properties related to it, such as syntactic mobility (possibility to occupy different positions in the clause), co-occurrence with other textual connection elements and ambiguity (situations in which appears the value conclusive and/or explicative to porém) and the fact that it can exercise other functions besides contrast/opposition, like correction, for example, on the other hand, we verified that it is described, basically, like contraposition operator, that orients the enunciation to contrary conclusions, eliminating previous arguments, making to prevail the arguments that it introduces. Thus, we ask: (i) in which positions porém occurs? (ii) which elements of textual connection porém co-occurs with? (iii) what functions porém exercise? (iv) when porém has argumentative force? (v) what is the kind of argumentative orientation exercised by porém? (vi) the Mobility, co-occurrence and ambiguity related to porém interfere how in its functions? (vii) the mobility, co-occurrence and ambiguity related to porém interfere how in its argumentative force and orientation? To answer these questions we selected 60 opinion articles, of four different on line newspapers of Brazil, which we obtained 73 instances of porém, and we used the computational program Goldvarb, for which we defined eight groups of factors. The analysis of the 73 occurrences of porém, based on the theoretical assumptions of Hopper (1991), Koch (2003; 2005), Neves (2000) e Perini (2006), led us to the following answers: (i) porém appears at first, between subject and verb, after the verb, at the end, before the subject, before the verb and between verbs of the second or last clause, and between names; (ii) porém co-occurs with elements of conditionality, mediation, comparison, temporality and correction or redefinition; (iii) porém exercise the function of the contrast, contraposition with elimination, contraposition in independent direction, correction, rectification, contraposition in the same direction, restriction, negation of the inference and compensation; (iv) porém always introduces the strongest arguments in the text; (v) porém orients the statements to same conclusion, to independent conclusion, to opposite conclusion, to contrary conclusion and to different conclusion; (vi) the co-occurrence and mobility of porém contributes to the semantic function of this operator. The ambiguity, in turn, reveals other values, not prototypical, to porém, which permits that this operator, in some of these cases, enter conclusion; (vii) the co-occurrence and mobility of porém reveals yourselves as syntactic resources offered by this linguistic element in favor of the argumentation, therefore, they interfere positively in its argumentative force and orientation. We conclude with this study that porém is used by writers, mainly, to the establishment of their opinions, from which they wish to convince the reader(s), and the form how porém is used show us that, justly, because porém relate properties of to two different grammatical classes, it offers multiple possibilities of use.